Legal Status Of Abandoned Land Pursued As Guarantee Under Law Number 4 Of 1996 Concerning Holding Rights - Noor, Aslan; Herlani, Lisa; Faridz Fathurrohman, Mohammad; Lorenza, Melinda; Nurwidianti, Maudy (Journal of Law, Politic and Humanities, 2024)
Economic Development is the most important part of National Development which seeks to improve all aspects of community, nation and state life to realize the National Goals of the Republic of Indonesia as stated in the 1945 Constitution of the Republic of Indonesia (1945 Constitution). In realizing National Development, quite a bit of capital is needed. One way to fulfill capital comes from banking sector credit. To provide this capital, banks require collateral to guarantee the return of funds from the credit that has been disbursed. Collateral is required if there is a default on the part of the debtor, then the bank as a creditor can sell the collateral to pay off the outstanding balance of the debtor's loan. The collateral most preferred by banks is usually in the form of fixed assets such as land because they have a fixed value and tend to increase from year to year. In reality, the land pledged by debtors to banks as creditors has the status of abandoned land. Abandoned land is land of rights, land of management rights and land obtained on the basis of land control, which is intentionally not cultivated, not used, not exploited and/or not maintained. As a result, if the debtor defaults, there is no special guarantee for the creditor as the holder of the mortgage rights.